Prevalence of hypertension and its association with obesity and socio-demographic factors among adults attending a tertiary care hospital in Bangladesh: a cross-sectional study - M. Mamun Khan; Amit Kumar Das; Jannat Mahozabeen; Sharmin Zaman Khan; Farhana Karim; Partha Sarathi Podder (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Hypertension is a major non-communicable disease and a leading risk factor for cardiovascular morbidity and mortality worldwide. Obesity is a well-established modifiable risk factor for hypertension, yet hospital-based evidence from Bangladesh remains limited. This study aimed to determine the prevalence of hypertension and its association with obesity and socio-demographic factors among adults attending a tertiary care hospital. Methods: A facility-based cross-sectional study was conducted among 340 adults attending a tertiary care hospital in Bangladesh. Participants were selected using simple random sampling. Data were collected through a structured questionnaire, along with anthropometric measurements and blood pressure assessment. Data were analyzed using SPSS version 26. Chi-square test and multivariable logistic regression were performed and p < 0.05 was considered statistically significant. Results: The prevalence of hypertension was 27.4%. A significant association was observed between BMI and hypertension (p=0.004). Participants aged >45 years had higher odds of hypertension (AOR=2.05, 95% CI: 1.20–3.50). Obesity was a strong independent predictor of hypertension (AOR=2.60, 95% CI: 1.50–4.50). Physical inactivity was also significantly associated with hypertension (AOR=1.60, 95% CI: 1.00–2.50). No significant association was found with gender, residence or religion. Conclusions: Hypertension is highly prevalent among adults attending tertiary care hospitals in Bangladesh and is significantly associated with obesity, older age and physical inactivity. Early screening and lifestyle modification strategies are essential to reduce the burden of hypertension.